Sisterland [large type] : a novel - Sittenfeld, Curtis (Thorndike Press, 2013)
When the strongest earthquake in U.S. history occurs just north of their St. Louis home, Kate and Jeremy find the disaster further complicated by Kate's self-proclaimed-medium twin's prediction about a more powerful earthquake, a situation that places Kate under public scrutiny and reveals her own psychic abilities.